2012
DOI: 10.11646/zootaxa.3548.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Rhaphium Meigen (Diptera, Dolichopodidae) from the Taimyr Peninsula (Russia), with description of a new species

Abstract: Eight species of Rhaphium Mg. are recorded from the southern tundra of the Taimyr Peninsula (Russia), including the description of a new species, Rhaphium borisovi Negrobov, Barkalov & Selivanova sp. nov. The new species is similar to Rhaphium gruniniani Negrobov and differs from it by yellow fore coxa, equal length of hind tarsomeres 1–2 and broader inner lobe of cercus. The female of Rhaphium beringiense Negrobov & Vockeroth is described. A key to Siberian species (exclusive of Far East species) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Recently Negrobov et al (2012) have found R. tripartitum on the Taimyr Peninsula (Zakharova Rassokha River, 72.7°N, 101.08°E). Negrobov has identified also a male from the middle part of the Yamal Peninsula as R. tripartitum (ZIN collection; Negrobov, pers.…”
Section: Rhaphium Tripartitum (Frey 1913) Figs 7-9mentioning
confidence: 99%
“…Recently Negrobov et al (2012) have found R. tripartitum on the Taimyr Peninsula (Zakharova Rassokha River, 72.7°N, 101.08°E). Negrobov has identified also a male from the middle part of the Yamal Peninsula as R. tripartitum (ZIN collection; Negrobov, pers.…”
Section: Rhaphium Tripartitum (Frey 1913) Figs 7-9mentioning
confidence: 99%
“…Negrobov (1979) published the last revision and key to the Palaearctic species of this genus. Since then the new species were described almost exclusively from eastern part of the Palaearctic Region, and Negrobov et al (2012) compiled a key to Siberian species, Negrobov et al (2020) published a key to species from Sakhalin and Kuril Islands, and Qilemoge et al (2020) provided the last key to Chinese species. The discovery of new European Rhaphium species is a rare event.…”
Section: Introductionmentioning
confidence: 99%
“…borisovi Negrobov, Barkalov et Selivanova, 2012, Rh. caucasicum Negrobov, Grichanov et Selivanova 2013(Negrobov 1986Negrobov and Onishchenko 1991;Negrobov and Grichanov 2010;Negrobov et al 2011Negrobov et al , 2012Negrobov et al , 2013b.…”
Section: Introductionmentioning
confidence: 99%